Evaluation of Serum Vitamin D Levels Among Patients with Viral Warts - Shamsa Kanwal; Farid ur Rehman; Bilqees Fatima; Sana Waqar Qureshi; Sibqa Jamil; Rab Nawaz Khan (Pakistan Armed Forces Medical Journal, 2023)
Objective: To evaluate serum levels of 25-hydroxyvitamin D (25-OHD) in patients with viral warts.